Studi Pengaruh Pengujian Solid Content Terhadap Karakteristik Tinta Sablon Alami Berbahan Dasar Kulit Buah Naga Meraheristik Tinta Sablon Alami Berbahan Dasar Kulit Buah Naga Merah - Fadhil Sukma Ramadhan; Emmidia Djonaedi; Rachmah Nanda Kartika (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2025)
Red dragon fruit peel contains betacyanin pigment, which has the potential as a natural colorant. This study aims to evaluate the effect of solid content on the characteristics of screen printing ink made from red dragon fruit peel. Solid content plays a crucial role in determining ink quality, particularly in terms of coverage and colorfastness. Three samples were prepared with varying pigment amounts: 10 grams (A1), 15 grams (A2), and 25 grams (A3), while the gum arabic content remained constant at 20 grams. The analysis showed that sample A2 had the highest solid content at 77.29%, followed by A3 (65.27%) and A1 (64.81%). Weight loss after oven drying showed A1 had the greatest reduction (1.33 grams), while A2 had the smallest (0.72 grams). These findings indicate that increasing pigment amounts enhances solid content, positively impacting coverage and color durability in natural screen printing ink.